ON TRANSVERSE VIBRATIONS OF A ROTATING-DISK OF UNIFORM STRENGTH - GUVEN, U (ASME-AMER SOC MECHANICAL ENG, 1992)
Transverse, axisymmetric vibrations of a rotating disk of uniform strength is studied. Closed-form solution for the equation of transverse motion is obtained in terms of confluent hypergeometric functions.
Keywords: Mechanics